The impact of tourism on occurrence of selected animal species in the Bohemian Forest - Dvořáková Líšková, Zuzana; Lapka, Miloslav; Cudlínová, Eva; Dvořák, Petr; Škodová Parmová, Dagmar (University of the Aegean, 2012)
Currently, the continuous expansion of urban areas is forcing people to move further into the countryside in search for open space. This results in decreasing of undisturbed natural areas which are slowly disappearing. This imbalance in the market, at least in Central Europe, leads to an increase in number of large protected areas preserved as recreational backgrounds for cities. The objective of this research was to assess the impact of tourism during one year on the selected fauna in the Bohemian Forest National Park (Šumava in Czech). Based on outdoor research, the stays signs of game were classified as well as particular activities of visitors were specified in the focused area to analyze the impact rate of visitors on the surrounding area.
Keywords: tourism; animal welfare; Bohemian Forest; environment